ANALISIS CARA BELAJAR SISWA MENGGUNAKAN MODEL DISCOVERY LEARNING PELAJARAN PPKn KELAS XI - Syahrowaldi, Hafizh Wahyu; Sastrawan, Agus; Utomo, Bambang Budi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe thesis entitled: The Analysis of Students' Learning Ways by Using Discovery Learning Model in PPKn Subject on the Eleventh Grade : The research design that used in this research is descriptive study with the form of qualitative research. The techniques of data collection that used in this research are through observation, interview and documentation. According to the result of data processing and the data analysis, it could be interpreted as follows: 1. Analyzed the whole data from the observation, interview and documentation in the form of pictures that taken in the learning activity. 2. Reduced the data by making the abstraction which is an effort to make the main conclusion, process and the statements that need to be kept in order to make it stay on the research domain. 3. Arranged the data into units. 4. Checked the research validity. 5. Interpreted the data, by processing the result of the research into the substantive theory that has been done in order to get the conclusion in the learning activity by using Discovery Learning model. According to the result of the research, it can be concluded that the application of Discovery Learning improve the argumentation skill and complex thinking in science .Keywords: Discovery Learning, Â Learning Ways, PPKn